Social and political ideas of B. R. Ambedkar : a study of his life, services, social and political ideas - Bharill, Chandra (Aalekh Publishers, 1977)
Biography of Bhimrao Ramji Ambedkar, 1892-1956, Indian social reformer and political leader.